2009
DOI: 10.1093/nar/gkp1105
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional transactivator Tat selectively regulates viral splicing

Abstract: HIV-1 gene expression requires both viral and cellular factors to control and coordinate transcription. While the viral factor Tat is known for its transcriptional transactivator properties, we present evidence for an unexpected function of Tat in viral splicing regulation. We used a series of HIV-1 reporter minigenes to demonstrate that Tat’s role in splicing is dependent on the cellular co-transcriptional splicing activators Tat-SF1 and CA150. Surprisingly, we show that this Tat-mediated splicing function is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 41 publications
2
46
1
Order By: Relevance
“…For example, the regulatory Tat and Rev proteins are produced from fully spliced transcripts. Tat enhances transcription from the viral LTR promoter (Das et al, 2011 and references therein) and influences splice site selection (Jablonski et al, 2010). Rev stimulates nuclear export of the unspliced and singly spliced viral RNAs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the regulatory Tat and Rev proteins are produced from fully spliced transcripts. Tat enhances transcription from the viral LTR promoter (Das et al, 2011 and references therein) and influences splice site selection (Jablonski et al, 2010). Rev stimulates nuclear export of the unspliced and singly spliced viral RNAs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Tat was shown to influence HIV-1 RNA splicing (38), capping (19,20,80), translation (15,16,18,68), and reverse transcription (3,36,43,44). Moreover, Tat has been proposed to modulate the expression of multiple cellular genes (reviewed in reference 63), to interact with a large number of cellular proteins (reference 32 and references therein), and to inhibit the cellular RNA interference mechanism (6,7,33,67).…”
mentioning
confidence: 99%
“…In recent work, we show that depletion of Tat-SF1 by gene silencing did not affect basal or Tat-dependent transcription from an HIV-1 CAT reporter in HeLa and HEK293 cells [66]. These data contradict the results obtained by Caputi and coworkers, which have recently reported that down-regulation of Tat-SF1 by siRNAs induces a decrease in transcription and Tat-mediated activation of an HIV-1 reporter minigene in HEK293 cells [67]. In this later work, the effect of reduction of TCERG1 expression was also analyzed.…”
Section: Discussionmentioning
confidence: 57%